Analysis of Digital Literacy Skills of Educators at MTA DDI Manding Polewali Mandar - Fiqri Ramadhan; Riana T Mangesa; Lu’mu Taris (PT. Global Research Collaboration, 2026)
This study aims to determine the level of digital literacy skills of teachers at MTs DDI Manding, Polman Regency. The research method used is quantitative research. This study applies descriptive statistical data analysis in presenting the results of data processing, using questionnaires and interviews in data collection, and using saturated sampling techniques to determine the research sample. The digital literacy skills of MTs DDI Manding teachers were reviewed from four aspects, namely Internet Searching, Hypertext Navigation, Content Evaluation, and Knowledge Assembly, and were still in the low category with a percentage of 39.38%, which indicates that teachers still lack self-development in the field of digital literacy. Based on the data collection results, it shows that the three factors that have a significant influence on teachers' digital literacy skills are Functional Skills, Communication and Interaction, and Critical Thinking. Data analysis shows that the average percentage of 22.79% is still in the insufficient category, indicating that the three factors that should support the improvement of digital literacy of MTs DDI Manding teachers are still in the insufficient category. The data collected by the researcher serves as a reference for MTs DDI Manding teachers to identify the factors that can support their digital literacy skills. The factors that influence an individual's digital literacy skills, in this case MTs DDI Manding teachers, can be used as a reference to further explore teachers' digital literacy skills to develop their creativity in teaching.